Persons Entitled to Asylum Create their Own Living Space – Conditions for a Successful Implementation in Rural Areas in Austria. Issue 10 (February 2019) - Fischer, Tatjana; Osterreicher, Doris
Abstract: The exodus from rural areas and subsequent migration into cities results in vacated housing and infrastructure substance, leaving behind valuable assets from a resource as well as building-heritage point of view. At the same time thousands of persons entitled to asylum are distributed on a quota-based and highly regulatory approach over the Austrian municipalities. From a spatial planning as well as from an architectural position, this raises several questions, which have been addressed in a research project funded under the Austrian Ministry of Europe, Integration and Foreign Affairs: (1) Can persons entitled to asylum be involved in the upgrading and refurbishment of vacant buildings with the purpose of creating their own living spaces? If so, which conditions are necessary for a successful cooperation? (Strategic point of view). (2) Which requirements must potentially adequate empty buildings fulfil in order to be suitable for this purpose? What are the relevant criteria related to building structure, location and infrastructure in this context? (Object-related point of view). (3) What would be the underlying business model based on a cooperation between local small and medium sized enterprises and persons entitled to asylum? (Economic point of view). The purpose of this paper is to present the different approaches of spatial planning and architecture, resulting in a subsequent common methodological approximation towards the joint topics of rural exodus, conservation of building stock and living space for persons entitled to asylum. Due to the sensitivity of the topic of migration and the complexity of the associated framework conditions, the assessment has been limited to an exemplary case study of a single rural municipality in Austria. The empirical results support the following findings: (1) Persons entitled to asylum are not perceived as a potential target group by the real estate market. (2) The requirements of local companies involved in building refurbishment actions do not match the potential of persons entitled to asylum, both from a quantitative as well as qualitative point of view. (3) The concept of matching rural vacancy and subsequent upgrading as well as refurbishment of buildings and the renewal of village centres in cooperation with persons entitled to asylum is currently not supported by the present legal framework conditions. Developing effective synergies between persons entitled to asylum creating their own living spaces and the declining rural population and subsequent building vacancy in rural Austria necessitates a viable legal, infrastructure related and market driven framework.